EFEKTIVITAS PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII PADA MATERI ALJABAR DI SMP NEGERI 14 SELUMA - Nopriani, Sara; Asiyah; Resti Komalasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model on the mathematical critical thinking ability of grade VII students on algebra material at SMP Negeri 14 Seluma. The background of this study is the low critical thinking ability of students in understanding and solving algebraic problems logically and reflectively. The method used was a pre-experimental design with a One Group Pretest-Posttest Design. The research subjects consisted of 29 students of class VII B, determined using a cluster random sampling technique. Data were collected using essay tests covering five critical thinking indicators based on Facione's (2011) theory, namely interpretation, analysis, evaluation, inference, and explanation. Data analysis employed the Shapiro-Wilk normality test, N-Gain percentage calculation, and the Paired Sample t-Test. The results showed that the mean posttest score was 86.21, higher than the mean pretest score of 38.97. The N-Gain percentage was 77.37%, categorized as high. The Paired Sample t-Test yielded a t-value of 30.258 with df = 28 and a Sig. (2-tailed) value of < 0.001, leading to the rejection of H0 and acceptance of Ha. Therefore, it is concluded that the implementation of the Problem Based Learning (PBL) model is significantly effective in improving the mathematical critical thinking ability of grade VII students on algebra material at SMP Negeri 14 Seluma.